Assessing the validity and reliability of the 10-item Persian version of the perceived stress scale in post-surgery patients - Sharif-Nia, Hamid; Froelicher, Erika Sivarajan; Hoseinzadeh, Esmail; Kaveh, Omolhoda; Fatehi, Reza; Nowrozi, Poorya (Frontiers in Psychiatry, 2024)
Introduction: The 10-item Perceived Stress Scale (PSS-10) is commonly used to measure stress levels in postoperative patients, as research shows that high levels of stress can affect postoperative outcomes. By using the PSS-10, healthcare providers can understand patients' psychological well-being before and after surgery, helping improve recovery and overall health. This study focuses on assessing the reliability and validity of the 10-item Persian version of the PSS (PSS-10-P) in postoperative patients. Methods: In a methodological study conducted between October to December 2023, a sample of 400 patients who had undergone surgery in 17 Shahrivar Hospital, Amol, Iran were selected using a convenience sampling method. The PSS-10 scale utilized in the study was translated, and its psychometric properties were evaluated through assessments of construct validity, including exploratory (n = 200) and confirmatory (n = 200) factor analysis, convergent validity, and discriminant validity. Furthermore, the study examined the internal consistency of the scale to ensure its reliability. Results: The mean age of the participants was 44.38 (SD= 13.49) years. The results of exploratory factor analysis with Promax rotation extracted two factors accounting for 83.82% of the variance comprising 10 items. After necessary modifications during CFA, the final model was approved. As for reliability, the Cronbach’s alpha, CR, and MaxR for all constructs were greater than 0.7, demonstrating good internal consistency and construct reliability. Conclusion: According to these results, the Persian version of PSS-10 has a valid structure and acceptable reliability. This scale can be used by health professionals in many ways.